Comparison glucose levels in capillaries and veins using glukometer in people with diabetes mellitus at community the geringging district the pariaman - Arniat Christinai Telaumbanua; Ibrahim Ibrahim Ibrahim; Mimi Mimi Susilawati (Stikes Syedza Saintika Padang, 2021)
Non-communicable diseases have now become a serious threat to global health, including diabetes. in reports from Sungai Geringging Public Health Center in 2020 the prevalence of diabetes mellitus was 450 people. Checking blood sugar levels in diabetic patients should be done regularly. Examination of blood glucose levels using the glucose oxidase method, examination materials in the form of venous blood and capillary blood. This study aims to determine the comparison of glucose levels in capillary and venous blood using a glucometer in patients with diabetes mellitus.This type of quantitative research was carried out at Sungai Geringging Public Health Center, Padang Pariaman Regency, and carried out in February 2021. The population of patients who did blood glucose checks with a sample of 81 people. Data analysis was univariate and bivariate using a t-test.The results of capillary blood glucose levels were 203.507 mg/dl, glucose levels in venous blood were 199.753 mg/dl. There is a difference in glucose levels in venous blood and capillary blood in respondents with v = 0.005 (α = 0.05). It was concluded that there was a difference in blood glucose levels in venous blood and capillary blood. It is recommended to increase the number of samples so that the accuracy of the research results can be maximized in further research.